Methods of diagnosing and restoring teeth abutments with different degrees of inclination in hard tissue defects and periodontal diseases. - I. V. Vyklyuk; Z. R. Ozhogan (Medičnì Perspektivi, 2014)
. The need of Ukrainian population in treating damaged parts of the tooth crown is 36-53 % of all patients, individually made root - casted cores are commonly used in practical dentistry. Using teeth roots for prosthesis has many advantages and allows to preserve integrity of the dentition, prevents premature atrophy of the alveolar bone and occurrence of dentoalveolar deformities. We have developed and practically implemented method of restoring tooth abutment by changing its axis in periodontal disease. During performing of the work we have carried out clinical examination of 127 patients with existing teeth and roots of teeth and periodontal disease. Defining of dentition parameters was performed by our method and by the proposed device, which determines angle of the root axis and its distance from the occlusal plane of dentition. As a result of our investigation, by measuring deviation of axis of crown tooth relatively dental arch, it was found that deviation from the axis in the vestibulo- oral direction prevailed within 3-7° in 1 degree of severity and 8-11° – in 2 degree of generalized periodontitis severity. By the results of measurements and X-ray examination one can assertain that roots with inclination of 3° to 15°, previously prepared endodontically, are suitable to restoration with adhesive root - crown systems as the base for orthopedic splinting constructions of dentures.